Boosting nitrogen-doping and controlling interlayer spacing in pre-reduced graphene oxides. (December 2020) - Ludwig, Tim; Je, Minyeong; Choi, Heechae; Fischer, Thomas; Roitsch, Stefan; Müller, Ralf; Mane, Rajaram S.; Kim, Kwang Ho; Mathur, Sanjay
Abstract: Controlling interlayer spacing in graphene oxide materials is an effective strategy to unify high conductivity with high intercalation and storage properties. Free-standing films of reduced graphene oxide (rGO) match these characteristics and are capable of replacing metal-based anodes in lithium-ion batteries (LIBs) crucially essential for enhanced flexibility and gravimetric energy density of devices currently sought for wearable and stretchable electronics. Restoring high electrical conductivity through chemical reduction of graphene oxide (GO) remains elusive due to interplay of desired in-plane conductivity and interlayer ion transport. A chemical pre-reduction step introduced in this work alleviated the defect density in graphene oxides to enable the incorporation of nitrogen by annealing in NH3 atmosphere. Decreased oxygen contents were observed upon pre-reduction through a deoxygenation process (C:O ratio GO: 1.7, rGO: 11.4, pre-reduced rGO: 34.8) to effectively restore the aromatic character in rGO films. The pre-reduction altered the chemical topography and reinforced the interlayer interactions of the resulting N:rGO films to boost the electrical conductivity (pre-reduced rGO: 11759 S m −1, pre-reduced N:rGO: 25253 S m −1 ) and produce more densely packed structures. DFT calculations confirmed a gradual decrease in interlayer spacing values in GO (4.85   Å ), N:rGO (3.83 Å ) and pre-reduced N:rGO* (3.61 Å ) samples, which validated the critical role of chemical pre-reduction. The DFT calculations also explained the differential behavior of N-doped and pre-reduced rGO films on significantly enhanced electrical conductivity and lithium storage capacity (rGO: 1208 S m −1, 261 mAh g −1 ; N:rGO: 10574 S m −1, 529 mAh g −1 ). This work presents a facile pathway to overcome the persisting limitation of 2D carbon nanostructures prepared by aqueous processing to produce chemically engineered graphitic carbons as anodes for lithium ion batteries. Graphical abstract: Image 1 Highlights: High-quality freestanding N:rGO electrodes obtained by pressure-based filtration of ammonia treated pre-reduced rGO. The pre-reduction step lowered the defect density and enhanced the deoxygenation process. DFT calculations predict the reduction of interlayer spacing among GO (4.85Å), N:rGO (3.83Å) and pre-reduced N:rGO* (3.61Å). Subtle interplay of chemical treatments and electronic properties of graphene oxide materials.